2017
DOI: 10.1002/jbm.b.33877
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and tissue integration of elastic mesh implants evaluated in vitro and in vivo

Abstract: The elastic properties of TPU mesh implants result in improved tissue integration compared to conventional PVDF meshes, and they adapt more efficiently to the abdominal wall. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 827-833, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Meshes for abdominal surgical procedures are flexible medical devices used to treat hernias, abdominal or inguinal, by adding tension-free reinforcement that results in improved tissue integration and reparation. , Meshes have also been used as prosthetic devices for the treatment of vaginal prolapse , and urinary incontinence . In the last decade, many fundamental research has been performed on tissue compatibility, bio-integration, and mechanical properties of surgical meshes. Also, their chemical surface functionalization has resulted in significant improvements, for example, prevention of unwanted tissue adhesion, cell adhesion/de-adhesion control features, and thermosensitive and shape memory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Meshes for abdominal surgical procedures are flexible medical devices used to treat hernias, abdominal or inguinal, by adding tension-free reinforcement that results in improved tissue integration and reparation. , Meshes have also been used as prosthetic devices for the treatment of vaginal prolapse , and urinary incontinence . In the last decade, many fundamental research has been performed on tissue compatibility, bio-integration, and mechanical properties of surgical meshes. Also, their chemical surface functionalization has resulted in significant improvements, for example, prevention of unwanted tissue adhesion, cell adhesion/de-adhesion control features, and thermosensitive and shape memory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in the repair and reconstruction of abdominal wall defects, the smoothness of the mesh after placement and the tightness with the abdominal wall are the key factors to reduce adhesion. [ 16,29 ] Tomaszewska et al. found that a mesh with higher elastic strength improved the dynamic properties of healing fascia and reduced abdominal adhesion compared to traditional PP meshes.…”
Section: Resultsmentioning
confidence: 99%
“…Once the bacteria are customized to the mesh to form infection, the immune cells in the body are difficult to enter and completely remove the bacteria, and a second operation is needed to remove the mesh. [ 15,16 ] In contrast, biomaterials such as ADM and small intestinal submucosa (SIS) can be used in infected areas to reduce the risk of inflammation and increase biocompatibility and reduce the risk of adhesion formation and hernia recurrences. [ 17,18 ] In addition, hydrogels meshes in abdominal hernia repairing showed good characteristics of promoting cell growth and forming vascularization tendency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] In addition, due to the limitation of process, the selected materials are usually a synthetic polymer with poor biological performance, so they often lead to pain, adhesion, and contraction with the surrounding tissues in patients in clinical practice. [6,26] Besides, the preparation process also has direct writing, pouring and so on. Although these processes can effectively prepare patches, they have shortcomings.…”
Section: Introductionmentioning
confidence: 99%